Socio-economic problems of the communicatively handicapped in India - Mohapied Fazlulla K (Journal of All India Institute of Speech and Hearing, 1970)
When the country's forty per cent of population is living below the poverty line; seventy per cent living in villages and when illiteracy is not lower than poverty, rehabilitation of the communicatively handicapped who form six per cent of the country's population becomes an extremely difficult task